Indicadores de sustentabilidade do Perímetro Irrigado de Betume - Nhampossa, Julieta Augusto (2015)
Irrigated agriculture has been of fundamental importance for food production in the Brazilian northeast. The public irrigation projects have emerged as response to drought problems harassing the Brazilian semi-arid region, and, to have success, it is imperative to reconcile the need of productivity goals with the social welfare and maintaining an ecologically healthy environment. The irrigated Bitumen perimeter, although not located in a semi-arid region, is a public irrigation project that aims to socioeconomic development of the region, whose main produced crop is flooded irrigated rice. Being so, this work aimed to analyze the sustainability of irrigated Bitumen perimeter through indicators in environmental, social and economic dimensions, in a horizon time of five years (2009-2014). For such, indicators were selected and measured based on Marco method for Assessment of Management Systems for Natural Resources Incorporating Sustainability Indicators (“MESMIS”), combined with the Hierarchical Analysis Technique (“AHP”), where the “MESMIS” was used for selection and measurement of indicators and the AHP helped the attribution of weights of the indicators. The results were obtained based on secondary data analysis provided by CODEVASF, company responsible for technical assistance of farmers on the perimeter. To each indicator was assigned a value that represents its performance, on scale from 0 (zero) to 10 (ten). This value was associated to the weight of each indicator to obtaining the sustainability index for each studied dimension. The general index perimeter of sustainability was obtained based on arithmetic mean of indices of the three dimensions. In this way, 20 indicators were selected, 7 of the environmental dimension, 6 of the social dimension, and 7 of the economic dimension, in that, the indices obtained by these dimensions were 3.81; 5.83; and 6.09; respectively. Therefore, the sustainability index for irrigated Bitumen perimeter in the period 2009-2014 was 5.24, which means that the perimeter is in a compromised sustainability situation. The indicators that received the most critical score are of environmental dimension was specifically the legal reserve area. However, the present research generated information that may contribute to the sustainable management of the Bitumen irrigation perimeter.